Burden of treatment in severe acne vulgaris - Lisa Kiely; Cathal O'Connor; Aysha Al Moosa; Emer Dight; Michelle Murphy (Wiley, 2024)
Abstract Background Acne is associated with a significant burden of disease related to the visual impact of facial lesions, symptoms such as pain, and sequelae such as scarring. However, little research has been performed on the acne‐specific burden of treatment (BOT), defined as the workload of healthcare as well as its impact on functioning and well‐being. Objectives The aim of this study was to examine the BOT of moderate‐severe acne. Methods A prospective study was performed in our tertiary dermatology department. Patients attending the dermatology department with moderate‐severe acne (defined as an Investigator's Global Assessment of acne severity of 3 or 4) were invited to complete a validated BOT questionnaire, modified for use in acne, with additional qualitative components. Results Of 50 patients, 68% were female, with a mean age of 22.6 years (range 16‐45 years). Most (82%, n = 41) patients were on isotretinoin, with 18% (n = 9) on oral antibiotics. The average BOT was 4.2/10 (range 0-8.2) for topical therapies, 4.5/10 (range 2.7-6.8) for oral antibiotics, and 3.8/10 (range 0.69-6.9) for isotretinoin. From qualitative statements, the greatest burdens reported with topical treatment were unpleasant sensations, skin sensitivity, skin dryness, and lack of efficacy; with antibiotic therapy were the requirement for long‐term treatment, limited efficacy, and side‐effects including gastrointestinal upset; and with isotretinoin therapy were cheilitis and xerosis, cost, and need for blood tests. However, 58% (n = 29) of patients believed their overall BOT was decreased with isotretinoin, and 18% (n = 9) felt that it was unchanged with isotretinoin, with statements such as "the side effects can be tough, but the result is definitely worth it." Conclusions The BOT associated with oral isotretinoin is similar or lower to topical therapies and oral antibiotics. This should be taken into consideration when optimizing the care of patients with acne.